Effect of an integral promotion program in the reduction of the risk for caries in school children in Angelópolis, Antioquia - Restrepo-S., Claudia Cecilia (Revista Facultad de Odontología Universidad de Antioquia, 2018)
The aim of the present study was to evaluate the effect of a multidimensional program for the promotion of oral health applied toa group of children (n=119) that are students of primary school. 98 children with the same characterisHcs that are studying in another school and didn't get even information about the program composed the control group. The program consisted mainly un education in oral health care, and was directed to the students, theirparents and teachers. The results were evaluated with COP-s, ceo-s, number of white lesions and with MEDI-MED, that gives information about the motivation of the child to visit the dentist, their gum's health, number of healthy permanent teeth and number of primary teeth with any grade of disease. The results were analyzecl with a multivan'ated arzalysis with logistíc regression in SP55' 8.0 for Windows and chisquare probe. The data taken before the application of the program showed that the main risk factors to acquire caries in permanent teeth are the white lesions and the lack of motivation to assist to the dental services. After the Promotional program, the motivation was enhanced, but still the white lesions appearto be a risk factor for caries in perrnanent teeth.